Punishment, Communication, and Community. - Duff, R. A. (Studies in crime and public policy., 2003)
The question "What can justify criminal punishment?" becomes especially insistent at times, like our own, of penal crisis, when serious doubts are raised not only about the justice or efficacy of particular modes of punishment, but about the very legitimacy of the whole penal system. Recent theorizing about punishment offers a variety of answers to that question-answers that try to make plausible sense of the idea that punishment is justified as being deserved for past crimes; answers that try to identify some beneficial consequences in terms of which punishment might be justified.